Interrupted time-series analysis to evaluate the impact of a national antimicrobial stewardship campaign on antibiotic prescribing: a typical practice in China’s primary care - Li, Hui; Gong, Yanhong; Han, Jing; Zhang, Shengchao; Chen, Shanquan; Xu, Xing; Lu, Zuxun; Yin, Xiaoxv (Clinical infectious diseases, 2021)
After implementing the 2011 national antimicrobial stewardship campaign, few studies focused on evaluating its effect in China’s primary care facilities.We randomly selected 11 community health centers in Shenzhen, China, and collected all outpatient prescriptions of these centers from 2010 to 2015. To evaluate the impact of local interventions on antibiotic prescribing, we used a segmented regression model of interrupted time series to analyze 7 outcomes (ie, percentage of prescriptions with antibiotics, and percentages of prescriptions with broad-spectrum antibiotics, with parenteral antibiotics, and with 2 or more antibiotics in all prescriptions or antibiotic-containing prescriptions).Overall, 1 482 223 outpatient prescriptions were obtained. The intervention was associated with a significant immediate change (-5.2%, P = .04) and change in slope (-3.1% per month, P < .01) for the percentage of prescriptions with antibiotics, and its relative cumulative effect at the end of the study was -74.0% (95% confidence interval, -79.0 to -69.1). After the intervention, the percentage of prescriptions with broad-spectrum and with parenteral antibiotics decreased dramatically by 36.7% and 77.3%, respectively, but their percentages in antibiotic-containing prescriptions decreased insignificantly. Percentage of prescriptions with two or more antibiotics in all prescriptions or antibiotic-containing prescriptions only showed immediate changes, but significant changes in slope were not observed.A typical practice in Shenzhen, China, showed that strict enforcement of the antimicrobial stewardship campaign could effectively reduce antibiotic prescribing in primary care with a stable long-term effect. However, prescribing of broad-spectrum and parenteral antibiotics was still prevalent. More targeted interventions are required to promote appropriate antibiotic use.